2022
DOI: 10.25100/prts.v0i35.12321
|View full text |Cite
|
Sign up to set email alerts
|

Identidades gestionadas: el caso de la Licenciatura en Trabajo Social en Chile

Abstract: En Chile, en el último lustro y en un contexto gerencial, las profesiones de la acción pública han experimentado profundas complejidades por variadas razones. Al respecto, tomando como caso de estudio al Trabajo Social, el artículo se pregunta sobre la relevancia de su Licenciatura en términos identitarios, y para aquello, se consideran discursos de profesionales que se desenvuelven en políticas vinculadas con Niñez, Protección y Vivienda Social. Todo lo precedente se analiza desde una propuesta teórica-metodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In these three locations, researchers built a non-random sample of 251 respondents (89 in Córdoba, 82 in Lima, and 80 in Montevideo) upon two variables: (1) religious self-identification segmented in four different categories: Catholics, Protestants (including mainline Protestants, Evangelicals, and Pentecostals), Other Traditions (Jewish, Mormons, Buddhists, Jehovah Witnesses, Adventists, Muslims, Umbanda), and Non-Affiliated (unaffiliated or disaffiliated believers, agnostic and atheist); and (2) socioeconomic status (SES) segmented in two categories: upper/middle, and lower SES. Investigators considered the religious affiliation as the one self-reported by the subjects at the moment of the first contact with them (as opposed to assigning the label of 'practicing' or 'nominal', as others have done; see Christian et al, 2015;Latinobarómetro, 2018;Valenzuela et al, 2007) and they balanced the sample in terms of gender and age since these features might influence their religious practices.…”
Section: Data Collection and Selection Of The Corpusmentioning
confidence: 99%
“…In these three locations, researchers built a non-random sample of 251 respondents (89 in Córdoba, 82 in Lima, and 80 in Montevideo) upon two variables: (1) religious self-identification segmented in four different categories: Catholics, Protestants (including mainline Protestants, Evangelicals, and Pentecostals), Other Traditions (Jewish, Mormons, Buddhists, Jehovah Witnesses, Adventists, Muslims, Umbanda), and Non-Affiliated (unaffiliated or disaffiliated believers, agnostic and atheist); and (2) socioeconomic status (SES) segmented in two categories: upper/middle, and lower SES. Investigators considered the religious affiliation as the one self-reported by the subjects at the moment of the first contact with them (as opposed to assigning the label of 'practicing' or 'nominal', as others have done; see Christian et al, 2015;Latinobarómetro, 2018;Valenzuela et al, 2007) and they balanced the sample in terms of gender and age since these features might influence their religious practices.…”
Section: Data Collection and Selection Of The Corpusmentioning
confidence: 99%